Can ICNP® be used in the process of nursing of patients with rheumatoid arthritis - Grabowska, Hanna (Nursing Problems / Problemy Pielęgniarstwa, 2015)
Introduction. Rheumatoid arthritis is a chronic, systemic inflammatory autoimmune disease with periods of exacerbation and remission. In the typical (developed) clinical picture of the patients, the symptoms of chronic rheumatoid arthritis are dominant: pain, swelling, limited mobility of the joints, as well as their morning stiffness. The disease causes disorders not only in the biological sphere — the progressing disability to perform daily activities, but also in terms of social life and mental health, causing the deterioration in the quality of life of patients. The objective of this study was an attempt to answer the question: can the International Classification for Nursing Practice (ICNP®) be used in the process of nursing of patients with rheumatoid arthritis? Material and methods. In this paper, a method of the analysis and critique of selected Polish literature from the last decade that included the aspects of nursing of patients with RA was used, and the cross-mapping of the diagnoses and nursing interventions with the use of the ICNP® dictionary (online version available on the International Council of Nurses site). Results and conclusions. All the key problems of the care of patients with RA (concerning physiological: pain, potential negative infection, potential negative medication side effect) and the activities undertaken in nursing them expressed in the traditional way were replaced with the ICNP® diagnoses and interventions. The use of terms from other classifications is an interesting proposal to supplement/complete the plan of care, and it also emphasizes the individual character of the service provided by the nurse.